2007
DOI: 10.1385/cbb:47:1:45
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hyperthyroidism on the effect of adenosine transport blockade assessed by a novel method in guinea pig atria

Abstract: The aim of the present study was to investigate the effect of hyperthyroidism on the trans-sarcolemmal adenosine (Ado) flux via equilibrative and nitrobenzylthioinosine (NBTI)-sensitive nucleoside transporters (ENT1) in guinea pig atria, by assessing the change in the Ado concentration of the interstitial fluid ([Ado]ISF) under nucleoside transport blockade with NBTI. For the assessment, we applied our novel method, which estimates the change in [Ado]ISF utilizing the altered inotropic response to N6-cyclopent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…Similarly to our earlier studies, the inotropic effect of adenosine and CPA was detected, because the contractile force proved to be a precisely measurable and informative output for quantifying the function of the A 1 receptor together with its postreceptorial signaling (Gesztelyi et al 2003(Gesztelyi et al , 2004Karsai et al 2006Karsai et al , 2007.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…Similarly to our earlier studies, the inotropic effect of adenosine and CPA was detected, because the contractile force proved to be a precisely measurable and informative output for quantifying the function of the A 1 receptor together with its postreceptorial signaling (Gesztelyi et al 2003(Gesztelyi et al , 2004Karsai et al 2006Karsai et al , 2007.…”
Section: Introductionsupporting
confidence: 62%
“…This assumption is supported by the previous observation of Collis et al (1989), who showed that, in the presence of EHNA, an adenosine deaminase inhibitor, and of dipyridamole, a nucleoside transport blocker capable of inhibiting the adenosine intake into the cardiomyocytes (Karsai et al 2006), the Schild analysis did provide a Schild slope not differing significantly from unity, when investigated the effect of CPX on adenosine E/c curves generated in guinea pig atria (Table 2). Since hyperthyroidism does not change direction of the transmembrane adenosine flux in the guinea pig atrium (Karsai et al 2007), intracellular actions of the exogenous adenosine could influence the effect of CPX in the T 4 -treated atria of the present study as well.…”
Section: Discussionmentioning
confidence: 61%
“…E/c curves that are suitable for RRM are XY graphs where X is the (logarithm of the) concentration of a pharmacological agonist, while Y is a response of a biological system that is evoked by the given agonist concentration (indicated by the corresponding X value) alone (first set of curves) or together with a single extra concentration (c x ) of the same or another agonist, which was administered to the system before the generation of the E/c curve (second set of curves). Quantifying this extra agonist concentration as a c x value is the goal of RRM [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…If the two agonists in question are the same, c x is a real concentration, and, if not, c x is a surrogate parameter of the single extra concentration of the other agonist [14,15]. The application of RRM might be useful when the concentration of this extra agonist is unknown and difficult to determine in any other manners [12,13]. As the single extra agonist concentration distorts (biases) the E/c curve in the second set as compared to the corresponding E/c curve in the first set (generated the same way except for the administration of the single extra agonist concentration), it will be referred to as "biasing" concentration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation